A comparison of most to least prompting, no‐no prompting and responsive prompt delay procedures. (28th June 2021) - Foran‐Conn, Denise; Hoerger, Marguerite; Kelly, Eimear; R. Cross, Richard; Jones, Serena; Walley, Hannah; Firth, Lauren
Abstract: Discrete trial training is a commonly used to teach children with autism spectrum disorder and related intellectual disabilities. A number of prompting and error correction strategies can be implemented when using discrete trial training. These strategies need to be effective and efficient. We compared a novel procedure, responsive prompt delay, to most to least prompting and no‐no prompting. A parallel treatments design, nestled in a modified multiple probe design (Horner & Baer, 1978), was used to compare the three procedures with three participants. The responsive prompt delay procedure was at least as effective as the most to least prompting and no‐no prompting procedures for three participants; the time required for each participant to master the skills was variable across procedures.